"Ser Piggy". Issue 1 (1st January 2015) - May, Karen; Upton, David
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this article is to explore Martin's apparent referencing of Golding's Lord of the Flies within his novel A Game of Thrones. This referencing centers on Martin's character Samwell Tarly, whose literary ancestor appears to be Golding's Piggy. A comparison of the two works suggests that Martin's work is in conversation with Golding's, particularly in the area of ethics, where the degeneration which occurs on Golding's "island" is contrasted with the strongly focused communality present at Martin's "Wall."